Inovasi Pengolahan Tutup Botol Sebagai Bahan Baku Alternatif Upcycle Art (IJM: Journal of Multidisiplinary, 2025)
Plastic waste especially bottle caps is a type of waste with high volume and significant utilization potential, yet it is often overlooked in environmental management. The public tends to discard bottle caps without reusing them, even though the material has strong physical properties and attractive color variations. This study aims to explore the use of bottle caps as an alternative raw material in upcycle art to produce artistic products that are both economically valuable and functional. The research employed a quantitative-descriptive approach through a production experiment method. The research subjects were a team of implementers who processed bottle caps using melting techniques with an oven and molding with custom molds. Data were collected through observation of the production process and cost analysis. Active participation from the local community was encouraged through workshop activities. The resulting products included keychains, coasters, and phone case decorations. The total production cost for one cycle was Rp 358,522, with a revenue of Rp 591,000 and a net profit of Rp 232,478. The findings indicate that processing bottle caps not only contributes to reducing plastic waste but also presents an opportunity for creative economic ventures based on community empowerment.